Symmetrized (p,h)-convexity and some Hermite-Hadamard-type inequalities - Lê, Bá Thông (Tay Nguyen Journal of Sciences, 2023)
This paper introduces symmetrized (p,h)-convex functions and establishes some Hermite-Hadamard-type inequalities for the new class of functions.